Introduction: Historiography and the philosophy of the sciences. (February 2016) - Hendry, Robin Findlay; Kidd, Ian James
Highlights: The history of science and the philosophy of science have a long and tangled relationship. Philosophical reflection on science can be guided, shaped, and challenged by historical scholarship. The activity of writing the history of science raises methodological questions which are the subject of continued debate in philosophy.